Perhitungan Efisiensi Biaya Produksi Tahu dengan Metode Heuristic Silver Meal - Muhammad Bayu Taufan; Eddy Eddy; Yetti Meuthia Hasibuan (JITEKH, 2021)
The research that was carried out was to calculate the efficiency of the production cost of tofu using the Heuristic Silver Meal method. For every tofu production, raw materials are needed. The raw materials needed to make tofu include imported soybeans and vinegar. The problem that often occurs in the Home Industry XYZ is that there is an excess supply of imported soybeans and vinegar which can cause ordering costs and storage costs for raw materials to increase. Things like this of course need to get serious attention and handling to improve the state of production activities of the home industry XYZ so as not to cause supply costs. With this problem, a research on the cost efficiency of Tofu Raw Material production is carried out in the hope that the Home industry XYZ can optimize inventory costs. the need for raw materials for making Tofu in order to maintain quality and streamline production costs. The results of the study using the Silver Meal Heuristic method were Rp. 315,059,416 and Meanwhile, using the riil method home industry is Rp. 307,741,100, from the comparison of the Silver Meal Heuristic method with the riil home industry method, the difference is Rp. 7,318,316 and the efficiency is 2.32%.